All‐Climate and Ultrastable Dual‐Ion Batteries with Long Life Achieved via Synergistic Enhancement of Cathode and Anode Interfaces. (14th February 2022) - Li, Wen‐Hao; Li, Yue‐Ming; Liu, Xin‐Fang; Gu, Zhen‐Yi; Liang, Hao‐Jie; Zhao, Xin‐Xin; Guo, Jin‐Zhi; Wu, Xing‐Long
Abstract: Dual‐ion batteries (DIBs) are a viable option for large‐scale energy storage owing to their high energy density, low cost, and environmental friendliness. However, interfacial instability at both the cathode and anode in Li‐graphite DIBs (LG‐DIBs) contributes to poor cycling performance and failed energy storage, severely limiting their application potentials. Herein, a two‐pronged strategy is used to improve the interfacial stability, synergistically stabilizing the graphite cathode by applying a rigid/inert surface coating while building a 3D framework on the lithium anode. The resultant LG‐DIBs are ultrastable and achieve a long cycle life (capacity retention of 80% after 2700 cycles at 200 mA −1 ) in the all‐climate temperature range from −25 to 40 °C. Ex situ characterization reveals that the cathode–electrolyte interphase on graphite is stabilized by suppressing the electrolyte decomposition and reducing graphite exfoliation. Simultaneously, the framework constructed on the lithium anode induces uniform and dendrite‐free Li deposition owing to its 3D structure. This study not only contributes to the development of practical LG‐DIBs but also points out a promising research direction for other new types of batteries. Abstract : A two‐pronged approach is adopted to modify and strengthen the anode electrolyte interphase and cathode electrolyte interphase synergistically in Li‐graphite dual‐ion batteries. The battery life is significantly enhanced in all climates from −25 to 40 °C by inducing homogeneous Li deposition and suppressing successive decomposition of the electrolyte on the graphite cathode.